Employing recent technologies for improved digital governance - Ponnusamy, Vasaki 1974-; Rafique, Khalid 1973-; Zaman, Noor 1972- (IGI Global, 2019)
"This book explores recent advances in the development, application, and impact of technologies in digital governance"--